Imbalanced Dermic Microbiome Aggravates Inflammation in Toenail Paronychia - Ying Li (Frontiers Media S.A., 2021)
The commensal microbiome influences skin immunity, but its function in toenail health remains unclear. Paronychia is one of the most common inflammatory toenail diseases, but antibiotic treatment is seldom effective in clinical cases. In this study, we performed 16S rRNA sequencing to investigate the characteristics of microbes associated with paronychia in order to identify the key microorganisms involved in inflammation. Seventy dermic samples were collected from patients with paronychia and the differences in dermic microbiota were analyzed in patients with different inflammation severities. Distinct clustering of dermal microbiota was observed in the dermis with different inflammation severities. A higher relative abundance of anaerobic microorganisms such as Parvimona, Prevotella, and Peptoniphilus was observed in severe paronychia, whereas Lactobacillus disappeared with disease progression. Co-occurring network analysis suggested that the disturbance of the dermic microbiome and attenuation of antagonism by Lactobacillus against anaerobic pathogens may aggravate inflammation in paronychia. Functional analysis showed that dermic microbiome disturbance may worsen microbial metabolism and tissue repair in the skin. In conclusion, we revealed that an increased abundance of anaerobic microorganisms and loss of Lactobacillus in the dermis may promote paronychia progression and microbiological imbalance may aggravate inflammation in patients with paronychia.